2014
DOI: 10.1016/j.jenvman.2013.12.005
|View full text |Cite
|
Sign up to set email alerts
|

The influence of farmer demographic characteristics on environmental behaviour: A review

Abstract: Many agricultural studies have observed a relationship between farmer demographic characteristics and environmental behaviours. These relationships are frequently employed in the construction of models, the identification of farmer types, or as part of more descriptive analyses aimed at understanding farmers' environmental behaviour. However, they have also often been found to be inconsistent or contradictory. Although a considerable body of literature has built up around the subject area, research has a tende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
122
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 204 publications
(130 citation statements)
references
References 89 publications
(129 reference statements)
6
122
1
1
Order By: Relevance
“…However, recent studies found mixed results for farmers' age, experience, education, and gender [56,71,77,79]. For example, Rahelizatovo and Gillespie [120] found that younger dairy producers tended to adopt BMPs more than older producers in Louisiana, whereas Tiwari et al [70] ascertained that age did not play a significant role in the adoption of improved soil conservation technology in Nepal.…”
Section: Demographics Knowledge and Attitudesmentioning
confidence: 99%
“…However, recent studies found mixed results for farmers' age, experience, education, and gender [56,71,77,79]. For example, Rahelizatovo and Gillespie [120] found that younger dairy producers tended to adopt BMPs more than older producers in Louisiana, whereas Tiwari et al [70] ascertained that age did not play a significant role in the adoption of improved soil conservation technology in Nepal.…”
Section: Demographics Knowledge and Attitudesmentioning
confidence: 99%
“…Farmers (and other rural actors) have been characterized as either legitimators or resistors of neoliberalism (Borras, 2010, Desmarais, 2007and Schneider and Niederle, 2010. Deeply embedded in both natural landscapes and neoliberal policies, farmers make daily choices regarding the management of property, land, and water -choices that are negotiated (Burton, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…age, sex, experience, property size, etc.) (BURTON, 2014;CELIO et al, 2014), (3) ins-titutional factors (e.g. fiscal and cognitive incentives, instrument regulation, commercial support -establishment of patterns of practices and environmental quality) (GREINER; GREGG, 2011), and (4) cognitive factors (e.g.…”
Section: Adherence To Environmental Policiesmentioning
confidence: 99%